Specificity and sensitivity assessment of selected nasal provocation testing techniques - Krzych-Fałta, Edyta; Furmańczyk, Konrad; Samoliński, Bolesław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: Nasal provocation testing involves an allergen-specific local reaction of the nasal mucosa to the administered allergen. Aim: To determine the most objective nasal occlusion assessment technique that could be used in nasal provocation testing. Material and methods : A total of 60 subjects, including 30 patients diagnosed with allergy to common environmental allergens and 30 healthy subjects were enrolled into the study. The method used in the study was a nasal provocation test with an allergen, with a standard dose of a control solution and an allergen (5,000 SBU/ml) administered using a calibrated atomizer into both nostrils at room temperature. Early-phase nasal mucosa response in the early phase of the allergic reaction was assessed via acoustic rhinometry, optical rhinometry, nitric oxide in nasal air, and tryptase levels in the nasal lavage fluid. Results : In estimating the homogeneity of the average values, the Levene’s test was used and receiver operating characteristic curves were plotted for all the methods used for assessing the nasal provocation test with an allergen. Statistically significant results were defined for p < 0.05. Of all the objective assessment techniques, the most sensitive and characteristic ones were the optical rhinometry techniques (specificity = 1, sensitivity = 1, AUC = 1, PPV = 1, NPV = 1). Conclusions : The techniques used showed significant differences between the group of patients with allergic rhinitis and the control group. Of all the objective assessment techniques, those most sensitive and characteristic were the optical rhinometry.